A qualitative analysis of perceptions of various stakeholders on nutrition-sensitive agricultural interventions, including the taxation on sugar-sweetened beverages (SSBs), to improve overall health and nutrition in South Africa - Tayla Ashton Kaltenbrun; Lisanne Monica du Plessis; Scott Drimie (BMC, 2020)
Abstract Background As a low-middle income country, South Africa has seen an upsurge in the double burden of malnutrition (DBM). Owing to the rising costs of obesity on healthcare in South Africa, the National Treasury implemented a fiscal policy for the taxation of SSBs, known as the Health Promotion Levy, in line with the WHO recommendation. Potential negative impacts of the policy on the sugar cane industry and economic and rural development have been voiced by different sectors. By including a subsection in the SSBs fiscal policy and aligning the goals with existing policies, government could have made provisions for sugar cane farms to substitute crops with alternatives, including nutritional alternatives where possible, while supporting existing small-scale farms to produce nutrient-dense, local and culturally acceptable crops. Thus, the purpose of the study is to understand the perceptions of the various stakeholders on combining nutrition-sensitive agricultural interventions with the taxation on sugar-sweetened beverages (SSBs) to improve overall health and nutrition in South Africa. Methods Semi-structured, in-depth interviews were conducted with each participant. The interviews were audio-recorded, transcribed intelligent verbatim, and cross-checked against the audio-recordings by the principal researcher. ATLAS.ti 8 software was used to navigate the data and assist with thematic analysis. Results Perceptions of combining SSB taxation with agricultural policies to improve food and nutrition security were positive. The participants found it to be an innovative idea in theory but questioned the feasibility of combining policies. Participants highlighted education as an essential element for successfully changing behaviour to ensure a positive impact of the combined policy approach. Participants believed that before government could scale up nutrition-sensitive agricultural interventions, basic services and government functions would first need to run optimally. Conclusion Overall, perceptions with regard to combining the taxation on SSBs with nutrition-sensitive agricultural policies to improve overall health and nutrition in South Africa were positive. Although participants questioned the feasibility of combining these policies, it was viewed as a way to combat alleged collateral damage linked to the tax, with a specific focus on developing small-scale farmers. More research into these combined policy approaches in a South African context is required.